2013
DOI: 10.5812/hepatmon.7382
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Diagnosis and Treatment Costs of Non-Alcoholic Fatty Liver Disease: A Two-Year Observation

Abstract: BackgroundThere are insufficient data available on utilization and health care costs of non-alcoholic fatty liver disease. The cost data for different health conditions and services is a major gap in Iranian health system. So this study is the primary or first step towards filling this gap.ObjectivesThis study aims to estimate the diagnosis and treatment costs of Non-alcoholic Fatty Liver.Patients and MethodsThis cross-sectional study was conducted on 528 subjects. The subjects had been diagnosed with non-alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…After following NAFLD patients (n = 528) for 2 years, the investigators calculated healthcare utilization costs based on the price lists approved in 2009-2011 by the Iranian Cabinet for the Public and Private Health Center and then converted the amount to PPP$. The authors reported an annual cost of PPP$1 billion as a result of having NAFLD and its associated comorbidities which was approximately PPP$5043 per individual patient with NAFLD [20]. Another study conducted in the West Suffolk area of the UK attempted to discern the costs of running their hepatology clinics.…”
Section: Publications Related To Economic Issues In Patients With Nonmentioning
confidence: 98%
See 3 more Smart Citations
“…After following NAFLD patients (n = 528) for 2 years, the investigators calculated healthcare utilization costs based on the price lists approved in 2009-2011 by the Iranian Cabinet for the Public and Private Health Center and then converted the amount to PPP$. The authors reported an annual cost of PPP$1 billion as a result of having NAFLD and its associated comorbidities which was approximately PPP$5043 per individual patient with NAFLD [20]. Another study conducted in the West Suffolk area of the UK attempted to discern the costs of running their hepatology clinics.…”
Section: Publications Related To Economic Issues In Patients With Nonmentioning
confidence: 98%
“…There is a remarkable paucity of data addressing economic issues in patients with NAFLD [16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Our search identified six articles related to the economics of NAFLD (four for the general population, one in the C65 years old or medically disabled population) (Table 1) [20,23,[30][31][32][33].…”
Section: Publications Related To Economic Issues In Patients With Nonmentioning
confidence: 99%
See 2 more Smart Citations
“…And also the other components of the MS, diabetes is more common among the Arab population than other regions of the world and is estimated to have increased rapidly in the region [81,91] . Approximately 50% of patients with T2DM also suffer from MS, whereas the risk of NAFLD in these patients is higher more than the other persons [94] .…”
Section: Msmentioning
confidence: 99%